The Multiple Rib Osteomyocutaneous Split Latissimus Dorsi Flap for Calvarial Reconstruction: Indication, Operative Technique, and Review of Literature. Issue 8 (28th November 2022) - Klein, Holger J.; Giovanoli, Pietro; Schweizer, Riccardo
Abstract : Major complex cranial defects may be challenging for the reconstructive microsurgeon. Affected patients often present with impaired soft tissues including dura exposure or fistulas. The lacking structural bony support may cause severe neurological issues and in select patients, there is a need for well-vascularized autologous tissue repair. The authors herein elucidate the role of the multiple rib osteomyocutaneous split latissimus dorsi flap for reconstruction of composite skull defects, providing an indication, an exemplary case, operation technique, and literature review. A 40-year-old woman after anaplastic oligodendroglioma resection suffered multiple extrusions and allograft cranioplasty infections. The defect was reconstructed with an osteomyocutaneus split latissimus dorsi flap including costae 3 ribs and a skin island. The included ribs were nourished via the anterior periosteum, while the posterior periosteum was left in place for the protection of the pleura parietalis. A proper amount of craniomedial latissimus dorsi muscle was spared to reduce donor site morbidity. The patient presented after 6 months with stable bony and soft tissue conditions without neurological symptoms, and acceptable donor site morbidity. After failed alloplastic cranioplasties, the free latissimus dorsi flap including vascularized ribs is well suitable for coverage of large compound cranial defects, providing skeletal support, improved contour, and enhanced functional outcome.